2011
DOI: 10.22270/jddt.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of SRM Microspheres of Repaglinide

Abstract: The aim of current work to develop and evaluate sustained release mucoadhesive (SRM) microspheres of Repaglinide using emulsification solvent evaporation technique. Effects of formulation variables i.e. polymer concentration and phase volume ratio on particle size, % mucoadhesion and drug release were investigated in this study. Scanning electron microscopy of microspheres with maximum drug content (Formulation CH1:8) demonstrated smooth surface spherical particles with mean diameter of 64.78 ± 3.26 μm. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Batch C1 showed the lowest EE% and this might be due to the fact that it had the smallest mean particle size. 33 It was also observed that increase in the drug concentration for the various batches brought about a corresponding increase in the EE% implying that the lipid matrix promoted concentration dependent encapsulation. 34 In vitro drug release.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Batch C1 showed the lowest EE% and this might be due to the fact that it had the smallest mean particle size. 33 It was also observed that increase in the drug concentration for the various batches brought about a corresponding increase in the EE% implying that the lipid matrix promoted concentration dependent encapsulation. 34 In vitro drug release.…”
Section: Resultsmentioning
confidence: 95%
“…This can result to increase in the viscosity of the system which in turn would require more energy to breakdown the droplets of the disperse phase. 33 The drug encapsulation efficiency was evaluated using spectrophotometric method and the EE% of the SLM was in the range of 62.22-99.05%, with batch C3 having the highest EE (99.05%). Batch C1 showed the lowest EE% and this might be due to the fact that it had the smallest mean particle size.…”
Section: Resultsmentioning
confidence: 99%